2008
DOI: 10.1136/emj.2007.053850
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department patient knowledge concerning acetaminophen (paracetamol) in over-the-counter and prescription analgesics

Abstract: Patient knowledge of the acetaminophen content of commonly used analgesic medications and its maximum recommended daily dose is limited. This may contribute to unintentional repeated supratherapeutic ingestion (RSTI) of acetaminophen, or overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
4
35
1
1
Order By: Relevance
“…But only 8 had the knowledge regarding the content of the brand and all except 9 had knowledge regarding the indication of the drug. Lack of knowledge regarding paracetamol content in the brands was quite similar to previous studies by Boudreau DM et al [15] who reported inadequate knowledge of drugs containing paracetamol and Fosnocht D [16] who reported that only 66-90% of 1009 patients in emergency department in a USA hospital had knowledge regarding the paracetamol contained in the common brands. But, the fact that our study participants were educated, contributed to their better awareness regarding the indication for use of the brand.…”
Section: Discussionsupporting
confidence: 86%
“…But only 8 had the knowledge regarding the content of the brand and all except 9 had knowledge regarding the indication of the drug. Lack of knowledge regarding paracetamol content in the brands was quite similar to previous studies by Boudreau DM et al [15] who reported inadequate knowledge of drugs containing paracetamol and Fosnocht D [16] who reported that only 66-90% of 1009 patients in emergency department in a USA hospital had knowledge regarding the paracetamol contained in the common brands. But, the fact that our study participants were educated, contributed to their better awareness regarding the indication for use of the brand.…”
Section: Discussionsupporting
confidence: 86%
“…Two previous US studies have shown that a significant proportion (6–25%) of those surveyed regularly exceed the maximum recommended daily dose of paracetamol 9 10. Additionally, patients have variable knowledge of which OTC and prescription analgesics contain acetaminophen (US generic name for paracetamol) 10.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies suggest many adults misinterpret OTC product instructions or not carefully heed them. [3][4][5][6] Recent attention has been focused on the unintentional misuse of OTC pain medication, and acetaminophen specifically, which is the most commonly-used OTC product in the U.S. with 19 % of adults reporting taking the drug in a given week. [7][8][9][10] Acetaminophen overdose is the leading cause of acute liver failure.…”
mentioning
confidence: 99%